2016
DOI: 10.1002/adfm.201604676
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Materials: A Case Study of the Effects of Metal Doping on ZnO Tetrapods with Bismuth and Tin Oxides

Abstract: Hybrid metal oxide nano-and microstructures exhibit novel properties, which make them promising candidates for a wide range of applications, including gas sensing. In this work, the characteristics of the hybrid ZnOBi 2 O 3 and ZnO-Zn 2 SnO 4 tetrapod (T) networks are investigated in detail. The gas sensing studies reveal improved performance of the hybrid networks compared to pure ZnO-T networks. For the ZnO-T-Bi 2 O 3 networks, an enhancement in H 2 gas response is obtained, although the observed p-type sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
114
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 156 publications
(117 citation statements)
references
References 86 publications
3
114
0
Order By: Relevance
“…The diameter of both structures (ZnO:Al MW and ZnAl 2 O 4 /ZnO MW) is ≈400 nm. In the case of the ZnO:Al MW a layered morphology is observed, which was demonstrated to be very efficient for the enhancement of the surface‐to‐volume ratio of MWs . This leads to a higher gas response due to a higher amount of adsorbed oxygen species .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diameter of both structures (ZnO:Al MW and ZnAl 2 O 4 /ZnO MW) is ≈400 nm. In the case of the ZnO:Al MW a layered morphology is observed, which was demonstrated to be very efficient for the enhancement of the surface‐to‐volume ratio of MWs . This leads to a higher gas response due to a higher amount of adsorbed oxygen species .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the formation of Schottky contacts based on Pd or Pt due to the high catalytic effect of such noble metals can induce the H 2 sensing properties, too, for such materials as carbon nanotubes (CNTs) and Si, which normally are not sensible to H 2 gas at room temperature . The detailed gas sensing mechanism with representation of the energy band diagram for individual structures with single and double Schottky contacts was presented in our previous works …”
Section: Resultsmentioning
confidence: 99%
“…Wei and co‐workers demonstrated that an increase in φ SB by adsorption of the oxygen at the Schottky contact area can lead to more than one order of magnitude of electrical current reduction . The gas mechanism of devices based on Schottky contacts was reported in previous work in detail . Thus, during exposure to ambient air, the φ SB will increase (φ SB + Δ, see Figure c) due to adsorption of oxygen species at the Schottky contact region (Equation ), leading to considerable decrease in the current through the conduction channel.…”
Section: Resultsmentioning
confidence: 99%
“…Rossinyol 15 and his co-workers proposed a better control of the performance of tungsten oxide based 2D hexagonal nanostructures as sensing materials. Postica et al 16 reported the advantage of a zinc oxide tetrapod network microstructure in the gas sensing technology with his co-authors. ZnO, which has a large direct optical band gap (E g ) of 3.2 eV with a hexagonal lattice is an important n-type semiconductor along with SnO 2 and TiO 2 .…”
Section: Introductionmentioning
confidence: 99%